ANALISA PRESSURE BUILD UP TEST PADA SUMUR X LAPANGAN Y DENGAN METODE HORNER MANUAL DAN ECRIN 4.10 - Agus Andri Yulianto; Djoko Sulistyanto; Albert Larope (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2015)
The main purpose of a hydrocarbons well testing or pressure transient analysis is to decide theability of a layer or formation to produce. Pressure transient analysis is basically giving a pressurebalance disorder on well tested. In this final thesis is conducted analysis of well test results atPressure Build Up with method Type Curve Pressure Deritative with help of software Ecrin v4.10and Horner Plot analysis manually.